Fabricating oxygen self-supplying 3D printed bioactive hydrogel scaffold for augmented vascularized bone regeneration - Yang Yang; Wanmeng Wang; Qianrui Zeng; Ning Wang; Wenbo Li; Bo Chen; Qingxin Guan; Changyi Li; Wei Li (Bioactive Materials, 2024)
Limited cells and factors, inadequate mechanical properties, and necrosis of defects center have hindered the wide clinical application of bone-tissue engineering scaffolds. Herein, we construct a self-oxygenated 3D printed bioactive hydrogel scaffold by integrating oxygen-generating nanoparticles and hybrid double network hydrogel structure. The hydrogel scaffold possesses the characteristics of extracellular matrix; Meanwhile, the fabricated hybrid double network structure by polyacrylamide and CaCl2-crosslinked sodium carboxymethylcellulose endows the hydrogel favorable compressive strength and 3D printability. Furthermore, the O2 generated by CaO2 nanoparticles encapsulated in ZIF-8 releases steadily and sustainably because of the well-developed microporous structure of ZIF-8, which can significantly promote cell viability and proliferation in vitro, as well as angiogenesis and osteogenic differentiation with the assistance of Zn2+. More significantly, the synergy of O2 and 3D printed pore structure can prevent necrosis of defects center and facilitate cell infiltration by providing cells the nutrients and space they need, which can further induce vascular network ingrowth and accelerate bone regeneration in all areas of the defect in vivo. Overall, this work provides a new avenue for preparing cell/factor-free bone-tissue engineered scaffolds that possess great potential for tissue regeneration and clinical alternative.